Testimony, Authority and Wisdom as Sources of Knowledge - Judycki, Stanisław (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The article takes into account the issue of sources of knowledge. The author distinguishes the concept of the source of knowledge in the sense of the origin of beliefs and in the sense of the basis for justification of beliefs. As sources of knowledge, he lists sensual perception, inner experience (introspection), memory, a priori cognition as well as testimony and authority. The concept of wisdom is also considered separately. In the matter of the nature of the testimony, the author argues in favor of the so-called antireductionism, and in relation to the nature of authority, authority is distinguished in a deontic and epistemic sense, and the thesis is formulated that epistemic authority is the basis of all other forms of authority, i.e. moral, political and religious. Wisdom is defined as axiological spirituality.